PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR ASET, INFLASI, DAN PDB TERHADAP STRUKTUR MODAL PADA PERUSAHAAN SEKTOR BASIC INDUSTRI AND CHEMICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2008-2014 - DIA MUSTIKA PERWITA, DWI (Jurnal Ilmu Manajemen (JIM), 2016)
The purpose of this research is to understand the influence of profitability, liquidity, assets structure, inflation, and gross domestic product on capital structure. In this research, researcher used Long-term Debt to Equity Rtio (LtDER) to measure capital structure. The object of this study were sector basic industry and chemicals company listed at Indonesia Stock Exchange 2008-2014 period. The methods of data analysis were multiple regression models. The result of this study indicated that, profitability variable has a negative influence on capital structure. Liquidity variable has no influence on capital structure. Assets structure variable has a positive influence on capital structure. Inflation variable has no influence on capital structure. And gross domestic product variable has no influence on capital structure. Keywords : capital structure, profitability, assets structure, basic industry and chemicals.